Efforts to increase dental and oral health knowledge for the people of Umbulmartani Village - Edwyn Saleh; Nadira Resya Nurhaliza; Vidya Shabrina Zata Amani; Dwi Aji Nugroho; Arief Waskitho; Sartika Puspita (Universitas Muhammadiyah Magelang, 2023)
Indonesian people's awareness of dental and oral health is still very low, this can be seen based on the number of people who go to the dentist only when experiencing dental and mouth problems. The purpose of this activity is to increase knowledge about dental and oral health in order to prevent increasing dental and oral health problems in Indonesia. The community service method in the first day, counseling was held on how to maintain healthy teeth and mouth, practice brushing teeth by distributing free toothbrushes and toothpaste. On the second day, free dental and general health treatment was carried out, starting with a vital sign examination and general check-up, followed by a dental and oral examination as well as basic medical treatment and procedures. The results of the service showed that there was an increase in knowledge about dental and oral health by avarage 86,5; 72 medical and 96 dental treatment. This activity ended with the distribution of free groceries to 90 heads of families.